My SQL - Fraser, Sophia (Global Media, 2011)
he modern solution to this problem is the database. A single entry is made for each country, for example, in a reference list that might be called the Country table. When someone needs to indicate the United Kingdom, he only has one choice available to him from the list: a single entry called "United Kingdom". In this example, "United Kingdom" is the unique representation of a country, and any further information about this country can use the same term from the same list to refer to the same country. For example, a list of telephone country codes and a list of European castles both need to refer to countries; by using the same Country table to provide this identical information to both of the new lists, we've established new relationships among different lists that only have one item in common: country. A relational database, therefore, is simply a collection of lists that share some common pieces of information.